Climate resilient livestock-based agro-forestry systems in north east india: productivity, carbon dynamics and livelihood implications - Murali Arthanari Palanisamy; Rajib Das; Joy Kumar Dey; Kiruthika Rajamanickam; Mahamaya Banik; Ajit Kumar Mandal; Jitendra Kumar; Shatabhisa Sarkar; Mainak Ghosh; Prasanta Kumar Pathak; A. K. Mohanty (Agroforestry Systems, 2026)

Pixel-Wise Analysis of Spatiotemporal Dynamics in Satellite-Derived Rainfall Trends Over Karnataka - S. Vigneshwaran; Abhishek A. Pathak; N. T. Vinod (Remote Sensing in Earth Systems Sciences, 2026)

Integrated pond co-culture of Penaeus vannamei with red seaweeds: Implications for nutrient uptake and dual production performance - K. Surya; Madhuri Pathak; Munilkumar Sukham; Thongam Ibemcha Chanu; Layana Porayil; Vaibhav A. Mantri; Debajit Sarma; G. Harini; P.S. Prathib; Bhavik Kantilal Bhagiya; Komal R. Chilveri (Algal Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Early-Middle Pleistocene to recent paleoceanographic variability in the Agulhas system (southwestern Indian Ocean) induced by fluctuations in the Antarctic Circumpolar Current - A.V. Del Gaudio; V.P. Singh; A. Arrigoni; X. Puentes-Jorge; R. Dwivedi; S. Pathak; A.R. Lam (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

Adverse childhood experiences, adult adiposity, and risk of young-onset breast cancer subtypes in a population-based case-control study - Lydia Marcus Post; Young Ik Cho; James Topitzes; DPhuong Do; Dorothy R. Pathak; Ann S. Hamilton; Amani M. Nuru-Jeter; Kelly A. Hirko; Jamila L. Kwarteng; Richard Houang; Ann G. Schwartz; Ellen M. Velie (Cancer Causes & Control, 2026)
Purpose Adverse childhood experiences (ACEs) are hypothesized to increase breast cancer risk via social and physiological pathways, yet associations between ACEs and young-onset breast cancer (BC) subtypes–and potential mediators (e.g., adiposity) of these associations–are largely unstudied. We sought to evaluate associations between ACEs and young-onset BC molecular subtypes, and the potential mediating effects of adiposity, in a population-based case–control study of invasive young-onset BC. Methods Cases (n = 1,754) were identified from the Los Angeles County and Metropolitan Detroit SEER registries, 2010–2015, and area-based, frequency-matched controls (n = 1,350) sampled from the 2010 Census. Associations between ACEs aged < 18 years and young-onset BC (diagnosed ages 20 to < 50 years), overall and by subtype (luminal A, luminal B, HER2 + , triple negative [TN]), were examined using weighted logistic regression. Adult adiposity (i.e., body mass index 12 months before diagnosis, waist circumference at interview) was evaluated as a mediator of these associations using weighted path analyses. Results ACEs (≥ 1 vs 0) were not significantly associated with young-onset BC (all p trend > 0.10); however, reporting one ACE (vs 0) was associated with TN (odds ratio [OR] = 1.85 [95% confidence interval [95%CI] = 1.08–3.16]). For individual ACEs, death of a loved one (vs 0 ACEs) was associated with HER2 + (OR = 2.50 [95%CI = 1.06–5.88]) and potentially TN (OR = 1.72 [95%CI = 0.96–3.10]) young-onset BC; other associations were non-significant. In path analyses, ACEs had a significant total effect on luminal A (β = 0.08, p = 0.03) and TN (β = 0.13, p < 0.01) tumors, with adiposity mitigating this association for luminal A tumors (β = -0.01, p = 0.04; TN β = 0.00, p > 0.05). Conclusions Bereavement during childhood was associated with higher odds of HER2 + young-onset BC, and there was some evidence of an association between ACEs and other young-onset BC subtypes, particularly TN.

Water Use in Rice Crop Cultivation in India: A Quantitative Assessment - Manish Debnath; Sumanta Chatterjee; A. K. Nayak; D. Chakraborty; H. Pathak (Agricultural Research, 2026)

Imperatorin, a natural furanocoumarin alleviates chronic neuropathic pain by targeting GABAergic tone in an animal model of spinal cord injury - Ayub Mohammed Butt; Manjeet Chopra; Ankita Bhagwani; Zarna Pathak; Kishori Jadhav; Rohini Jadhav; Pooja Tarde; Parusu Kavya Teja; Suraj Kutre; A. Hariharan; Alisha Vartak; Siddheshwar K. Chauthe; et al. (Natural Product Research, 2026)

Associations of glyphosate and aminomethylphosphonic acid (AMPA) concentrations with birth outcomes in pregnant women from the Midwestern U.S. - Kelsi A. Morris; Maria E. Cinzori; Brad A. Ryva; Nicole Talge; Khyatiben V. Pathak; Brooke Lovell; Patrick Pirrotte; Susan L. Schantz; Rita S. Strakovsky (International Journal of Hygiene and Environmental Health, 2026)

Elucidating the Conjoint Effect of Nano, Conventional and Bio-Fertilizer on Steering Sugarcane Productivity, Quality and Soil Health - Mona Nagargade; Vishal Tyagi; Dileep Kumar; Sudhir Kumar Shukla; Preeti Singh; Rajeev Kumar; Ashwini Dutt Pathak; V. P. Jaiswal; M. K. Tripathi; A. P. Dwivedi; Lalan Sharma; Sanjay Singh Rathore; et al. (International Journal of Plant Production, 2026)

Review of Nano-clay Polymer Composites for Controlled Nitrogen Release: Prospects and Limitations - Bitish Kumar Nayak; Dibyendu Chatterjee; Ranjan Paul; Saikat Ranjan Das; Totan Adak; Nintu Mandal; Julia Drewer; Abhijit Pradhan; Manik Chandra Kundu; Asit Kumar Pal; Gour Hari Santra; Suryakanta Sahoo; et al. (Agricultural Research, 2025)
This review paper discusses the potential and limitations of polymer composites for smart nitrogen (N) supply to meet the needs of agricultural crops. Unlike most conventional fertilizers, nano-clay polymer composites (NCPCs) offer a slow-release mechanism that enhances nitrogen use efficiency and reduces its loss to the environment. NCPCs are normally synthesized using solution blending, melt blending and in situ polymerization. Solution blending offers a better clay dispersion in the polymer matrix than melt blending owing to its low viscosity and strong stirring force. NCPCs have been characterized by several techniques, including equilibrium water absorbency, Fourier transform infrared spectroscopy, scanning electron microscopy, X-ray diffraction and nutrient release kinetics. The potential benefits of using these composites are highlighted, including improved nitrogen use efficiency and reduced environmental impacts, as are their prospects for widespread use in agriculture and mitigation of the adverse environmental effects from conventional fertilizers. In addition, the limitations of NCPC technology, such as cost, scalability and potential negative environmental effects, are also investigated. The paper provides a wide perspective on the NCPC technology, including the regulatory environment and policy, industry trends and commercialization potential. NCPCs offer many benefits to increase nitrogen use efficiency and reduce pollution affecting water quality, air quality and climate. The main current barrier to overcome is to reduce production costs, so that farmers may also benefit financially from the higher nitrogen use efficiency and associated reduced amounts of nitrogen wasted to the environment.

Retraction Note: Nanosilver-functionalized polysaccharides as a platform for wound dressing - Syam Mohan; Pranay Wal; Kamla Pathak; Madhusmruti Khandai; Tapan Behl; Hassan A. Alhazmi; Gulrana Khuwaja; Asaad Khalid (Environmental Science and Pollution Research, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Detection of elevated CO₂ and CH₄ emissions from power plant and landfill sites using airborne and spaceborne imaging spectroscopy - Hasmukh K. Varchand; Mehul R. Pandya; Jalpesh A. Dave; Parthkumar N. Parmar; Dhruv D. Desai; Manoj Singh; Dhiraj B. Shah; Vishal N. Pathak; Himanshu J. Trivedi (Atmospheric Pollution Research, 2025)

Enhancement of vitamin B12 in plant-based food through microbial fermentation-a sustainable food system - Gitanjali S. Deokar; Vaishnavi A. Pathak; Sanjay J. Kshirsagar; Fahad Al-Asmari; Nilesh Nirmal (Food Chemistry, 2025)

Impact of abiotic factors on different developmental stages of Antheraea proylei (Lepidoptera: Saturniidae) reared on Quercus floribunda and Q. glauca - Gunjan Pathak; Himanshu Pande Lohani; Jeetika Siddhu; B. R. Kaushal; A. S. Verma (International Journal of Tropical Insect Science, 2025)

Integration of Bioproducts with NPK for Improving Physiological Efficiency of Sugarcane and Sustaining Soil Quality Parameters in Subtropical India - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; A. D. Pathak; Asha Gaur; Abhay Srivastava; Rishi Kumar; Mamta Chaoudhary (Sugar Tech, 2025)

Habitat suitability mapping of chocolate mahseer, Neolissochilus hexagonolepis (McClelland, 1839) in the Teesta River basin, Indian Himalayan region for conservation - Vijay Kumar; Ganesan Kantharajan; Lalit Kumar Tyagi; Achal Singh; Rejani Chandran; A. K. Pathak; Amit Singh Bisht; L. Mog Chowdhury; Rajeev K. Singh; Uttam Kumar Sarkar (Spatial Information Research, 2025)

Lumpy skin disease virus (LSDV) infection in free-ranging red serow (Capricornis rubidus), Mizoram, India - Tridib Kumar Rajkhowa; Kiran Jayappa; Charitha B. Balakrishna; Laldinliana Khiangte; A. Z. Beithatlo; Mamta Pathak (European Journal of Wildlife Research, 2025)

Integration of Mycorrhizae, Azotobacter and Pseudomonas spp (PSB) with NPK and their Effects on Sugarcane Crop and Soil Health in Uttar Pradesh, India - M. K. Tripathi; S. K. Shukla; V. P. Jaiswal; Lalan Sharma; Mona Nagargade; A. D. Pathak; A. P. Dwivedi; Ankur Tripathi; V. K. Singh; V. P. Singh; Ajay Ranka (Sugar Tech, 2025)

NADPH Oxidases in Cancer Therapy-Induced Cardiotoxicity: Mechanisms and Therapeutic Approaches - Ayat Hussein Adhab; Farag M. A. Altalbawy; Morug Salih Mahdi; Lalji Baldaniya; Thabit Moath Omar; Subbulakshmi Ganesan; Bhanu Juneja; Piyus Kumar Pathak; Aseel Salah Mansoor; Usama Kadem Radi; Nasr Saadoun Abd; Munther Kadhim (Cardiovascular Toxicology, 2025)

Modified emission and scaling factors for methane and nitrous oxide in rice system of India: A country specific disaggregate approach - Pratap Bhattacharyya; A. Bhatia; N. Jain; D. Chatterjee; S. Mohanty; M. Prabhakar; Pratibha M; N.N. Jambhulkar; S. Ananthakrishnan; S.K. Nayak; A.K. Nayak; H. Pathak (Journal of Environmental Management, 2025)

Integrating socio-economic variables in urban flood damage assessments: a case study of Bengaluru, India - Abhishek A. Pathak; Apoorva R. Mathad; Alexandre S. Gagnon (Natural Hazards, 2025)

Dynamic monitoring of surface soil moisture fluctuations using synthetic aperture radar and data-driven algorithms - Hrushikesh Rajeev; Punithraj Gururaj; Abhishek A Pathak (Applied Geomatics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Evaluation of energy consumption data for business consumers - Anchal Pathak; A. Deivasree Anbu; Azlin Binti Abd Jamil; Sunil Kumar Vohra; Shashi Kant Gupta; Ashish Kumar Pandey; Getnet Worke Abate (Environment, Development and Sustainability, 2025)

A hybrid physics-based method for estimating land surface temperature using radiative transfer simulations and machine learning model from Sentinel-3A SLSTR observations - Jalpesh A. Dave; Vedant Pandya; Frank-M. Goettsche; Hasmukh K. Varchand; Parthkumar N. Parmar; Dhruv D. Desai; Disha B. Kardani; Dhiraj B. Shah; Ashwin Gujrati; Vishal N. Pathak; Himanshu J. Trivedi; Mehul R. Pandya (Earth Science Informatics, 2025)

Zinc Adsorption–Desorption Behavior and Sequential Extractable Pools in Sugarcane-Based Cropping Systems of Western Indo-Gangetic Plain - Shivam Singh; Satendra Kumar; Debashis Dutta; Richa Raghuvanshi; Jagannath Pathak; Uday Pratap Shahi; B. P. Dhyani; Ankit Kumar; Mahendra Pratap Singh; Himanshu Panday; A. K. Shah (Sugar Tech, 2024)

Genetic Profiling of Spodoptera litura (Noctuidae: Lepidoptera) in Indian Sub-Tropical Sugar Beet - Santeshwari Srivastava; Varucha Misra; Arun Baitha; Himanshu Pandey; S. N. Sushil; M. Mohan; A. D. Pathak; Sangeeta Srivastava; Dinesh Singh; Ashutosh Kumar Mall (Sugar Tech, 2024)

Retrieving Surface and Rootzone Soil Moisture Using Microwave Remote Sensing - Santhosh Kumar Thaggahalli Nagaraju; Abhishek A. Pathak (Journal of the Indian Society of Remote Sensing, 2024)

Reducing the environmental impact of rice production in subtropical India by minimising reactive nitrogen loss - Dibyendu Chatterjee; Saikat Ranjan Das; Sangita Mohanty; Baishnab Charan Muduli; Arti Bhatia; Bitish Kumar Nayak; Robert M. Rees; Julia Drewer; Amaresh Kumar Nayak; Tapan Kumar Adhya; Chidambaranathan Parameswaran; Jitendriya Meher; et al. (Journal of Environmental Management, 2024)

Inclusion of organic and inorganic extractive species improves growth, survival and physiological responses of GIFT fish reared in freshwater integrated multi-trophic aquaculture system - S.V. Shinde; K.S. Sukhdhane; K.K. Krishnani; B. Rani A. M.; M.S. Pathak; T.I. Chanu; S. Munilkumar (Aquaculture, 2024)

Adoption of Trench Method Cane Planting and its Role in Increasing Cane Yield and Sugar Recovery in Uttar Pradesh - S. K. Pathak; R. A. Kushwaha; A. K. Sah (Sugar Tech, 2024)

Lifetime alcohol consumption patterns and young-onset breast cancer by subtype among Non-Hispanic Black and White women in the Young Women’s Health History Study - Kelly A. Hirko; Darek R. Lucas; Dorothy R. Pathak; Ann S. Hamilton; Lydia M. Post; Ugonna Ihenacho; Nicole Bohme Carnegie; Richard T. Houang; Kendra Schwartz; Ellen M. Velie (Cancer Causes & Control, 2024)

CO2 concentration retrieval and emission rate estimation over Indian thermal power plants using radiative transfer approach and AVIRIS-NG data - Hasmukh K. Varchand; Mehul R. Pandya; Jalpesh A. Dave; Parthkumar N. Parmar; Himanshu J. Trivedi; Dhiraj B. Shah; Vishal N. Pathak (Remote Sensing Applications: Society and Environment, 2024)

Distribution and concentration pathway of particulate pollution during pandemic-induced lockdown in metropolitan cities in India - A. Anand; V. K. Garg; A. Agrawal; S. Mangla; A. Pathak (International Journal of Environmental Science and Technology, 2024)

Comparative evaluation of native top feeds of western Himalayas for utilization as goat’s ration in mash and block form - Imran Ahmad Ganai; R. K. Sharma; Ankur Rastogi; A. K. Pathak; Vijay Kumar Sharma (Tropical Animal Health and Production, 2023)

Co-applied Nitrogen and Auxin via Nano-clay-Polymer Composites Enhances Yield and Nitrogen Use Efficiency - Dibyendu Chatterjee; Totan Adak; Bitish Kumar Nayak; Ranjan Paul; Abhijit Pradhan; Mark A. Sutton; Julia Drewer; Saikat Ranjan Das; Amaresh Kumar Nayak; Himanshu Pathak (Journal of Soil Science and Plant Nutrition, 2023)

Characterisation of geranylgeranyl diphosphate synthase from the sandfly Lutzomyia longipalpis - Charles Ducker; Stanley French; Monika Pathak; Harry Taylor; Adam Sainter; William Askem; Ingrid Dreveny; Antônio Euzébio Goulart Santana; John A. Pickett; Neil J. Oldham (Insect Biochemistry and Molecular Biology, 2023)

The impact of different fertiliser management options and cultivars on nitrogen use efficiency and yield for rice cropping in the Indo-Gangetic Plain: Two seasons of methane, nitrous oxide and ammonia emissions - Arti Bhatia; Nicholas J. Cowan; Julia Drewer; Ritu Tomer; Vinod Kumar; Shikha Sharma; Ankita Paul; Niveta Jain; Sandeep Kumar; Girish Jha; Renu Singh; Radha Prasanna; et al. (Agriculture, Ecosystems & Environment, 2023)

Adoption of cleaner technologies and reduction in fire events in the hotspots lead to global decline in carbon monoxide - A. Joshi; M. Pathak; J. Kuttippurath; V.K. Patel (Chemosphere, 2023)

Potential avenue of genetic engineered algal derived bioactive compounds: influencing parameters, challenges and future prospects - Richa Kothari; Har Mohan Singh; Rifat Azam; Kajol Goria; Anu Bharti; Anita Singh; Somvir Bajar; Ashish Pathak; A. K. Pandey; V. V. Tyagi (Phytochemistry Reviews, 2023)

Phenome-wide genetic-correlation analysis and genetically informed causal inference of amyotrophic lateral sclerosis - Salvatore D’Antona; Gita A. Pathak; Dora Koller; Danilo Porro; Claudia Cava; Renato Polimanti (Human Genetics, 2023)
Leveraging genome-wide association statistics generated from a large study of amyotrophic lateral sclerosis (ALS; 29,612 cases and 122,656 controls) and UK Biobank (UKB; 4,024 phenotypes, up to 361,194 participants), we conducted a phenome-wide analysis of ALS genetic liability and identified 46 genetically correlated traits, such as fluid intelligence score ( r g = − 0.21, p = 1.74 × 10 –6 ), "spending time in pub or social club” ( r g = 0.24, p = 2.77 × 10 –6 ), non-work related walking ( r g = − 0.25, p = 1.95 × 10 –6 ), college education ( r g = − 0.15, p = 7.08 × 10 –5 ), “ever diagnosed with panic attacks ( r g = 0.39, p = 4.24 × 10 –5 ), and “self-reported other gastritis including duodenitis” ( r g = 0.28, p = 1.4 × 10 –3 ). To assess the putative directionality of these genetic correlations, we conducted a latent causal variable analysis, identifying significant genetic causality proportions (gĉp) linking ALS genetic liability to seven traits. While the genetic component of “self-reported other gastritis including duodenitis" showed a causal effect on ALS (gĉp = 0.50, p = 1.26 × 10 –29 ), the genetic liability to ALS is potentially causal for multiple traits, also including an effect on "ever being diagnosed with panic attacks” (gĉp = 0.79, p = 5.011 × 10 –15 ) and inverse effects on “other leisure/social group activities” (gĉp = 0.66, p = 1 × 10 –4 ) and prospective memory result (gĉp = 0.35, p = 0.005). Our subsequent Mendelian randomization analysis indicated that some of these associations may be due to bidirectional effects. In conclusion, this phenome-wide investigation of ALS polygenic architecture highlights the widespread pleiotropy linking this disorder with several health domains.

Enhancing Crop Productivity and Profitability of Autumn Sugarcane with Intercropping of Winter Vegetables in Real Farming Situations of North-Central India - S. N. Singh; Chandra Gupta; V. K. Singh; A. D. Pathak; A. K. Sah; M. K. Tripathi; Sanjiv Gupta; J. R. Patnaik (Sugar Tech, 2023)

RETRACTED ARTICLE: Nanosilver-functionalized polysaccharides as a platform for wound dressing - Syam Mohan; Pranay Wal; Kamla Pathak; Madhusmruti Khandai; Tapan Behl; Hassan A. Alhazmi; Gulrana Khuwaja; Asaad Khalid (Environmental Science and Pollution Research, 2023)

Energy and exergy analyses of fabricated pyramid type solar distillation plant for optimization: An experimental work - A. Geete; S. Rathore; V. K. Pathak (International Journal of Energy and Water Resources, 2023)

Thyroid hormone dynamics of Tharparkar and Sahiwal cattle during induced heat stress - Anjali; Gururaj VK; Lipika Sarma; M. Tripathi; Med Ram Verma; Vinay Verma; M. C. Pathak; H. A. Samad; V. P. Maurya; V. S. Chouhan; Gyanendra Singh (Tropical Animal Health and Production, 2023)

Crop Residue Recycling Affecting Carbon Sequestration, Nutrients Availability and Crop Yields in Rice–Wheat and Sugarcane–Ratoon–Wheat System - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; A. D. Pathak (Sugar Tech, 2023)

Adsorption of congo red using carbon from leaves and stem of water hyacinth: equilibrium, kinetics, thermodynamic studies - A. Extross; A. Waknis; C. Tagad; V. V. Gedam; P. D. Pathak (International Journal of Environmental Science and Technology, 2023)

Increasing clinician participation in tobacco cessation by an implementation science-based tobacco cessation champion program - Cary A. Presant; Kimlin Ashing; Sophia Yeung; Jonjon Macalintal; Brian Tiep; Argelia Sandoval; Susan Brown; Mary Cianfrocca; Loretta Erhunmwunsee; Dan Raz; Arya Amini; Ravi Salgia; et al. (Cancer Causes & Control, 2023)

Breeding for Drought Tolerance in Sugarcane: Indian Perspective - A. K. Mall; Varucha Misra; A. D. Pathak; Sangeeta Srivastava (Sugar Tech, 2022)

Improved Aerosolization Stability of Inhalable Tobramycin Powder Formulation by Co-Spray Drying with Colistin - Vaibhav Pathak; Heejun Park; Dmitry Zemlyanov; Sonal V. Bhujbal; Maizbha Uddin Ahmed; Mohammad A. K. Azad; Jian Li; Qi Tony Zhou (Pharmaceutical Research, 2022)

Climatology and model prediction of aerosol optical properties over the Indo-Gangetic Basin in north India - Amarendra Singh; Sumit Singh; A. K. Srivastava; Swagata Payra; Virendra Pathak; A. K. Shukla (Environmental Monitoring and Assessment, 2022)

Plant Quarantine Regulations With Reference to Sugarcane in India: Strengths and Challenges - S. N. Sushil; Deeksha Joshi; Sharmila Roy; G. P. Rao; A. D. Pathak (Sugar Tech, 2022)

Transcriptomic Insight into Aroma Pathway Genes and Effect of Ripening Difference on Expression of Aroma Genes in Different Mango Cultivars - Garima Pathak; Shivanand Suresh Dudhagi; Saumya Raizada; Vidhu A. Sane (Plant Molecular Biology Reporter, 2022)

Diversification Options in Sugarcane-Based Cropping Systems for Doubling Farmers’ Income in Subtropical India - S. K. Shukla; Lalan Sharma; V. P. Jaiswal; A. P. Dwivedi; S. K. Yadav; A. D. Pathak (Sugar Tech, 2022)

Expression of stable and reliable preference and aversion phenotypes following place conditioning with psychostimulants - Ritu A. Shetty; Margaret Rutledge; Alison LeBouf; James T. Mock; Gita Pathak; Michael J. Forster (Psychopharmacology, 2022)

Prolonged effects of DPP-4 inhibitors on steato-hepatitic changes in Sprague–Dawley rats fed a high-cholesterol diet - Rashmi Pathak; Avinash Kumar; Henry A. Palfrey; Kirsten P. Stone; Narayan R. Raju; Thomas W. Gettys; Subramanyam N. Murthy (Inflammation Research, 2022)

An investigation into the role of synoptic conditions on Central African precipitation variability - Sinclaire Zebaze; Raju Pathak; A. J. Komkoua Mbienda; Wilfried Pokam Mba; Popat Salunke; Abhishek Anand; Derbetini Appolinaire Vondou; André Lenouo; Saroj Kanta Mishra (Acta Geophysica, 2022)

Blood Circulatory Level of Seven Sirtuins in Alzheimer’s Disease: Potent Biomarker Based on Translational Research - Rashmita Pradhan; Abhinay Kumar Singh; Pramod Kumar; Swati Bajpai; Mona Pathak; Prasun Chatterjee; Sadanand Dwivedi; A. B. Dey; Sharmistha Dey (Molecular Neurobiology, 2022)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Sugar Beet Cultivation in India: Prospects for Bio-Ethanol Production and Value-Added Co-Products - Ashutosh Kumar Mall; Varucha Misra; Santeshwari; A. D. Pathak; Sangeeta Srivastava (Sugar Tech, 2021)

Spent marigold flower meal as an alternate feed for goats - Gagandeep Kour; R. K. Sharma; Nazam Khan; A. K. Pathak; Ankur Rastogi; Vijay Kumar Sharma (Tropical Animal Health and Production, 2021)

Vertical distribution analysis of soil organic carbon and total nitrogen in different land use patterns of an agro-organic farm - Priyadarshani Pathak; A. S. Reddy (Tropical Ecology, 2021)

Management of Termites Through Different Tools and Their Impact on Environment and Soil Micro-arthropods in Sugarcane in Indo-Gangetic Plains of India - S. N. Sushil; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Identification of Appropriate Agri-technologies Minimizing Yield Gaps in Different Sugarcane-Growing States of India - S. K. Shukla; Lalan Sharma; V. P. Jaiswal; A. D. Pathak; S. K. Awasthi; Adil Zubair; S. K. Yadav (Sugar Tech, 2021)

Effect of Long-Term Organic Fertilization in Flooded Rice Soil on Phosphorus Transformation and Phosphate Solubilizing Microorganisms - Dibyendu Chatterjee; A. K. Nayak; Annapurna Mishra; C. K. Swain; U. Kumar; D. Bhaduri; P. Panneerselvam; B. Lal; P. Gautam; H. Pathak (Journal of Soil Science and Plant Nutrition, 2021)

Potassium Influencing Physiological Parameters, Photosynthesis and Sugarcane Yield in Subtropical India - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; Ishwar Singh; A. D. Pathak; Mona Nagargade; Arup Ghosh; C. Gupta; Asha Gaur; S. K. Awasthi; Raghvendra Tiwari; Abhay Srivastava; et al. (Sugar Tech, 2021)

Selection and validation of differentially expressed metabolic and immune genes in weaned Ghurrah versus crossbred piglets - A. Karthikeyan; Shalu Kumari Pathak; Amit Kumar; B. A. A Sai Kumar; Aamir Bashir; Akansha Singh; N. R. Sahoo; B. P. Mishra (Tropical Animal Health and Production, 2021)

Incidence and Diversity of Termites Associated with Sugarcane in North-West Zone of India with New Records - S. N. Sushil; C. M. Kalleshwaraswamy; M. Ranjith; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Sugarcane Yield Using Minimum Tillage Technology Through Subsoiling: Beneficial Impact on Soil Compaction, Carbon Conservation and Activity of Soil Enzymes - S. K. Shukla; V. P. Jaiswal; Lalan Sharma; A. D. Pathak; Akhilesh Kumar Singh; Rajendra Gupta; S. K. Awasthi; Asha Gaur; Adil Zubair; Raghvendra Tiwari (Sugar Tech, 2020)

Characterization of bioaerosols in Northeast India in terms of culturable biological entities along with inhalable, thoracic and alveolar particles - Binita Pathak; Debajit Borah; Ankita Khataniar; P K Bhuyan; A K Buragohain (Journal of Earth System Science, 2020)

Comparison of Meteorological Drought Indices for Different Climatic Regions of an Indian River Basin - Abhishek A. Pathak; B. M. Dodamani (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Trend analysis of rainfall, rainy days and drought: a case study of Ghataprabha River Basin, India - Abhishek A. Pathak; B. M. Dodamani (Modeling Earth Systems and Environment, 2020)

Foliar Spray of Synthetic Osmolytes Alleviates Terminal Heat Stress in Late-Sown Wheat - A. Roy Chowdhury; M. Ghosh; M. Lal; A. Pal; K. K. Hazra; S. Acharya; A. Chaurasiya; S. K. Pathak (International Journal of Plant Production, 2020)

Determination of Morphological and Biochemical Basis of Resistance Against Top Borer, Scirpophaga excerptalis Walker in Sugarcane - S. N. Sushil; Amaresh Chandra; Sharmila Roy; A. K. Jaiswal; M. R. Singh; A. D. Pathak (Sugar Tech, 2020)

Process of fruit peel waste biorefinery: a case study of citrus waste biorefinery, its environmental impacts and recommendations - Saurabh N. Joglekar; Pranav D. Pathak; Sachin A. Mandavgane; Bhaskar D. Kulkarni (Environmental Science and Pollution Research, 2019)

Evaluation of a fusion gene-based DNA prime-protein boost vaccination strategy against Newcastle disease virus - Sagar A. Khulape; Hemanta Kumar Maity; Dinesh Chandra Pathak; Narayan Ramamurthy; Saravanan Ramakrishnan; Madhan Mohan Chellappa; Sohini Dey (Tropical Animal Health and Production, 2019)

Trend Analysis of Groundwater Levels and Assessment of Regional Groundwater Drought: Ghataprabha River Basin, India - Abhishek A. Pathak; B. M. Dodamani (Natural Resources Research, 2019)

The incretin enhancer, sitagliptin, exacerbates expression of hepatic inflammatory markers in rats fed a high-cholesterol diet - Rashmi Pathak; Avinash Kumar; Henry A. Palfrey; Laura A. Forney; Kirsten P. Stone; Narayan R. Raju; Thomas W. Gettys; Subramanyam N. Murthy (Inflammation Research, 2019)

Green Technologies for Improving Cane Sugar Productivity and Sustaining Soil Fertility in Sugarcane-Based Cropping System - S. K. Shukla; S. Solomon; Lalan Sharma; V. P. Jaiswal; A. D. Pathak; Priyanka Singh (Sugar Tech, 2019)

Ecosystem services in different agro-climatic zones in eastern India: impact of land use and land cover change - Rahul Tripathi; K. C. Moharana; A. D. Nayak; B. Dhal; Md Shahid; B. Mondal; S. D. Mohapatra; P. Bhattacharyya; Nuala Fitton; Pete Smith; A. K. Shukla; H. Pathak; et al. (Environmental Monitoring and Assessment, 2019)

Understanding the role of moisture transport on the dry bias in indian monsoon simulations by CFSv2 - A. S. Sahana; Amey Pathak; M. K. Roxy; Subimal Ghosh (Climate Dynamics, 2019)

Laser-induced breakdown spectroscopy (LIBS): a novel technology for identifying microbes causing infectious diseases - Vivek K. Singh; Jitendra Sharma; Ashok K. Pathak; Charles T. Ghany; M. A. Gondal (Biophysical Reviews, 2018)

Application of BICOVOX catalyst for hydrogen production from ethanol - S. Sharma; B. Patil; A. Pathak; S. Ghosalkar; H. K. Mohanta; B. Roy (Clean Technologies and Environmental Policy, 2018)

RNA Seq analysis for transcriptome profiling in response to classical swine fever vaccination in indigenous and crossbred pigs - Shalu Kumari Pathak; Amit Kumar; G. Bhuwana; Vaishali Sah; Vikramadiya Upmanyu; A. K. Tiwari; A. P. Sahoo; A. R. Sahoo; Sajjad A. Wani; Manjit Panigrahi; N. R. Sahoo; Ravi Kumar (Functional & Integrative Genomics, 2017)

Soil Carbon Sequestration and Crop Yields in Rice–Wheat and Sugarcane–Ratoon–Wheat Cropping Systems Through Crop Residue Management and Inoculation of Trichoderma viride in Subtropical India - S. K. Shukla; Swaha Shee; S. K. Maity; S. Solomon; S. K. Awasthi; Asha Gaur; A. D. Pathak; V. P. Jaiswal (Sugar Tech, 2017)

Control of campylobacter in poultry industry from farm to poultry processing unit: A review - Pramila Umaraw; A. Prajapati; Akhilesh K. Verma; V. Pathak; V. P. Singh (Critical Reviews in Food Science and Nutrition, 2017)

Crop Diversification Options Involving Pulses and Sugarcane for Improving Crop Productivity, Nutritional Security and Sustainability in India - S. K. Shukla; K. K. Singh; A. D. Pathak; V. P. Jaiswal; S. Solomon (Sugar Tech, 2017)

Habitat Fingerprinting Using Otolith Trace Metal Profile of Two Catfish Species of Genus Ompok (Siluridae) from Ganges Basin, India - U. K. Sarkar; A. K. Pathak; B. K. Gupta; D. D. Patra (Proceedings of the Zoological Society, 2016)

Super-Optimal NPK Along with Foliar Iron Application Influences Bioavailability of Iron and Zinc of Wheat - Rajiv Rakshit; A. K. Patra; T. J. Purakayastha; R. D. Singh; H. Pathak; Shiva Dhar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Cysteine-rich secretory protein 3 plays a role in prostate cancer cell invasion and affects expression of PSA and ANXA1 - Bhakti R. Pathak; Ananya A. Breed; Snehal Apte; Kshitish Acharya; Smita D. Mahale (Molecular and Cellular Biochemistry, 2016)

Indirect organogenesis from leaf explants of Hemidesmus indicus (L.) R. Br.: an important medicinal plant - A. R. Pathak; A. G. Joshi (Plant Biosystems, 2015)

Development of GIS-based fuzzy pattern recognition model (modified DRASTIC model) for groundwater vulnerability to pollution assessment - J. Iqbal; A. K. Gorai; Y. B. Katpatal; G. Pathak (International Journal of Environmental Science and Technology, 2015)

Accumulation of heavy metals in the vegetables grown in wastewater irrigated areas of Dehradun, India with reference to human health risk - A. K. Chopra; Chakresh Pathak (Environmental Monitoring and Assessment, 2015)

Development of hierarchical fuzzy model for groundwater vulnerability to pollution assessment - Jawed Iqbal; Gopal Pathak; A. K. Gorai (Arabian Journal of Geosciences, 2015)

Ascorbic acid at pre-anthesis modulate the thermotolerance level of wheat (Triticum aestivum) pollen under heat stress - Ranjeet R. Kumar; Suneha Goswami; Kritika A. Gadpayle; Khushboo Singh; Sushil K. Sharma; G. P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2014)

Sugar Beet: A Historical Perspective in Indian Context - A. D. Pathak; Raman Kapur; S. Solomon; Rajesh Kumar; Sangeeta Srivastava; P. R. Singh (Sugar Tech, 2014)

Evaluation of Engineered Geothermal Systems as a Heat Source for Oil Sands Production in Northern Alberta - V. Pathak; T. Babadagli; J. A. Majorowicz; M. J. Unsworth (Natural Resources Research, 2014)

Infections do not predict shedding in co‐infections with two helminths from a natural system - Isabella M. Cattadori; Benjamin R. Wagner; Laura A. Wodzinski; Ashutosh K. Pathak; Adam Poole; Brian Boag (Ecology, 2014)
Given the health and economic burden associated with the widespread occurrence of co‐infections in humans and agricultural animals, understanding how co‐infections contribute to host heterogeneity to infection and transmission is critical if we are to assess risk of infection based on host characteristics. Here, we examine whether host heterogeneity to infection leads to similar heterogeneity in transmission in a population of rabbits single and co‐infected with two helminths and monitored monthly for eight years. Compared to single infections, co‐infected rabbits carried higher Trichostrongylus retortaeformis intensities, shorter worms with fewer eggs in utero, and shed similar numbers of parasite eggs. In contrast, the same co‐infected rabbits harbored fewer Graphidium strigosum with longer bodies and more eggs in utero, and shed more eggs of this helminth. A positive density‐dependent relationship between fecundity and intensity was found for T. retortaeformis but not G. strigosum in co‐infected rabbits. Juvenile rabbits contributed to most of the infection and shedding of T. retortaeformis , while adult hosts were more important for G. strigosum dynamics of infection and transmission, and this pattern was consistent in single and co‐infected individuals. This host–parasite system suggests that we cannot predict the pattern of parasite shedding during co‐infections based on intensity of infection alone. We suggest that a mismatching between susceptibility and infectiousness should be expected in helminth co‐infections and should not be overlooked.

Characterization of smallholder pig production system: productive and reproductive performances of local and crossbred pigs in Sikkim Himalayan region - B. G. Nath; P. K. Pathak; S. V. Ngachan; A. K. Tripathi; A. K. Mohanty (Tropical Animal Health and Production, 2013)

Accumulation of heavy metals in Spinacia oleracea irrigated with paper mill effluent and sewage - Chakresh Pathak; A. K. Chopra; Sachin Srivastava (Environmental Monitoring and Assessment, 2013)

Agro-potentiality of distillery effluent on soil and agronomical characteristics of Abelmoschus esculentus L. (okra) - A. K. Chopra; Sachin Srivastava; Vinod Kumar; Chakresh Pathak (Environmental Monitoring and Assessment, 2013)

Enrichment and Translocation of Heavy Metals in Soil and Spinacea oleracea Grown in Sugar Mill Effluent Irrigated Soil - A. K. Chopra; Chakresh Pathak (Sugar Tech, 2013)

Particulate matter concentration in ambient air and its effects on lung functions among residents in the National Capital Region, India - C. Kesavachandran; B. S. Pangtey; V. Bihari; M. Fareed; M. K. Pathak; A. K. Srivastava; N. Mathur (Environmental Monitoring and Assessment, 2013)

Differential expression of heat shock protein and alteration in osmolyte accumulation under heat stress in wheat - Ranjeet R. Kumar; Suneha Goswami; Sushil K. Sharma; Khushboo Singh; Kritika A. Gadpayle; S. D. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2013)

Dry direct-seeding of rice for mitigating greenhouse gas emission: field experimentation and simulation - H. Pathak; S. Sankhyan; D. S. Dubey; A. Bhatia; N. Jain (Paddy and Water Environment, 2013)

Development of fuzzy air quality index using soft computing approach - T. Mandal; A. K. Gorai; G. Pathak (Environmental Monitoring and Assessment, 2012)

Ammonia emission from subtropical crop land area in India - A. Datta; S. K. Sharma; R. C. Harit; V. Kumar; T. K. Mandal; H. Pathak (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Bioaccumulation and Translocation Efficiency of Heavy Metals in Vegetables Grown on Long-Term Wastewater Irrigated Soil Near Bindal River, Dehradun - A. K. Chopra; Chakresh Pathak (Agricultural Research, 2012)

Freshwater fish biodiversity in the River Ganga (India): changing pattern, threats and conservation perspectives - U. K. Sarkar; A. K. Pathak; R. K. Sinha; K. Sivakumar; A. K. Pandian; A. Pandey; V. K. Dubey; W. S. Lakra (Reviews in Fish Biology and Fisheries, 2012)

QSAR analysis of Mur B inhibitors with antibacterial properties discussing role of physico-chemical parameters - A. K. Srivastava; Vinay Kumar Pathak; Archana; Meetu Jaiswala; Vijay K. Agrawal (Medicinal Chemistry Research, 2011)

Effect of Zinc Supplementation on the Status of Thyroid Hormones and Na, K, and Ca Levels in Blood Following Ethanol Feeding - R. Pathak; D. Dhawan; A. Pathak (Biological Trace Element Research, 2011)

Maternal and cord blood levels of Aldrin and Dieldrin in Delhi population - MD. Mustafa; Rahul Pathak; A. K. Tripathi; Rafat S. Ahmed; Kiran Guleria; B. D. Banerjee (Environmental Monitoring and Assessment, 2010)

Intake and utilization of sorghum and maize green fodder in spotted deer under captivity - A. Sahoo; A. K. Garg; B. M. Arora; N. N. Pathak (Tropical Animal Health and Production, 2010)

Isolation and characterization of Indian isolates of camel pox virus - V. Bhanuprakash; V. Balamurugan; M. Hosamani; G. Venkatesan; Bina Chauhan; V. A. Srinivasan; R. S. Chauhan; K. M. L. Pathak; Raj Kumar Singh (Tropical Animal Health and Production, 2010)

Molecular assessment of genetic diversity in cluster bean (Cyamopsis tetragonoloba) genotypes - Rakesh Pathak; S. K. Singh; Manjit Singh; A. Henry (Journal of Genetics, 2010)

Soil–plant–animal continuum in relation to macro and micro mineral status of dairy cattle in subtropical hill agro ecosystem - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Brajendra; T. Ramesh (Tropical Animal Health and Production, 2010)

Trade-off between productivity enhancement and global warming potential of rice and wheat in India - A. Bhatia; H. Pathak; P. K. Aggarwal; N. Jain (Nutrient Cycling in Agroecosystems, 2010)

Nitrogen, phosphorus, and potassium budgets in Indian agriculture - H. Pathak; S. Mohanty; N. Jain; A. Bhatia (Nutrient Cycling in Agroecosystems, 2010)

Diagnosis of gastrointestinal tuberculosis: Using cytomorphological, microbiological, immunological and molecular techniques — A study from Central India - Pradyumna Kumar Mishra; A. Bhargava; R. P. Punde; N. Pathak; P. Desikan; A. Jain; S. Varshney; K. K. Maudar (Indian Journal of Clinical Biochemistry, 2010)

Segment-2 sequence analysis and cross-neutralization studies on some Indian bluetongue viruses suggest isolates are VP2-variants of serotype 23 - Prabhakar A. Tembhurne; Bimalendu Mondal; Kunj B. Pathak; Sanchay K. Biswas; Aniket Sanyal; Mahendra P. Yadav; Santanu K. Bandyopadhyay; Raj K. Singh (Archives of Virology, 2010)

Integrated resource-driven pig production systems in a mountainous area of Northeast India: production practices and pig performance - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Anubrata Das; R. K. Bardoloi (Tropical Animal Health and Production, 2009)

Eco-restoration of a high-sulphur coal mine overburden dumping site in northeast India: A case study - J. Dowarah; H. P. Deka Boruah; J. Gogoi; N. Pathak; N. Saikia; A. K. Handique (Journal of Earth System Science, 2009)

Global warming mitigation potential of biogas plants in India - H. Pathak; N. Jain; A. Bhatia; S. Mohanty; Navindu Gupta (Environmental Monitoring and Assessment, 2009)

Novel blue light‐sensitive proteins from a metagenomic approach - G. P. Pathak; A. Ehrenreich; A. Losi; W. R. Streit; W. Gärtner (Environmental Microbiology, 2009)
Summary A microarray‐based approach was used to screen a soil metagenome for the presence of blue light (BL) photoreceptor‐encoding genes. The microarray carried 149 different 54‐mer oligonucleotides, derived from consensus sequences of light, oxygen and voltage (LOV) domain BL photoreceptor genes. Calibration of the microarrays allowed the detection of minimally 50 ng of genomic DNA against a background of 2–5 μg of genomic DNA. Identification of a positive cosmid clone was still possible for an amount of 0.25 ng against a background of 10 μg of labelled DNA clones. The array could readily identify targets carrying 4% sequence mismatch. Using the LOV microarray, up to 1200 library clones in concentrations of c . 20 ng each with a c . 40 kb insert size could be screened in a single batch. After calibration and reliability controls, the microarray was probed with cosmid‐cloned DNA from the thermophilic fraction of a soil sample. From this approach, a novel gene was isolated that encodes a protein consisting of several Per‐Arnt‐Sim domains, a LOV domain associated to a histidine kinase and a response regulator domain. The novel gene showed highest similarity to a known sequence from Kineococcus radiotolerans SRS30216 (58% identity for the LOV domain only) and to a gene from Methylibium petroleiphilum PM1 (57% identity). The gene, designated as ht‐met1 (Hamburg Thermophile Metagenome 1), was isolated and fully sequenced (3615 bp). ht‐met1 is followed by a second open reading frame encoding a Fe‐chelatase, an arrangement quite frequent for BL photoreceptors. The LOV domain region of ht‐met1 was subcloned and expressed yielding a fully functional, flavin‐containing LOV domain. Irradiation generated the typical LOV photochemistry, with the transient formation of a flavin‐protein photoadduct. The dark recovery lifetime was found as τ REC = 120 s (20°C) and is among the fastest ones determined so far for bacterial LOV domains.

Mineral profiling of local pig-feeds and pigs reared under resource driven production system to reduce porcine mineral deficiency in subtropical hill ecosystem of Northeastern India - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Anubrata Das; T. Ramesh (Tropical Animal Health and Production, 2009)

Analysis of integrated animal-fish production system under subtropical hill agro ecosystem in India: Growth performance of animals, total biomass production and monetary benefit - A. Kumaresan; K. A. Pathak; K. M. Bujarbaruah; K. Vinod (Tropical Animal Health and Production, 2009)

Reproductive performance of crossbred dairy cows reared under traditional low input production system in the eastern Himalayas - A. Kumaresan; P. P. Prabhakaran; K. M. Bujarbaruah; K. A. Pathak; Bijoy Chhetri; S. K. Ahmed (Tropical Animal Health and Production, 2009)

Effect of growth regulators on in vitro multiplication and rooting of shoot cultures in sugarcane - Shweta Pathak; M. Lal; A. K. Tiwan; M. L. Sharma (Sugar Tech, 2009)

Reproductive pathways of seed development in apomictic guinea grass (Panicum maximum Jacq.) reveal uncoupling of apomixis components - P. Kaushal; D. R. Malaviya; A. K. Roy; Shalini Pathak; A. Agrawal; Ambica Khare; S. A. Siddiqui (Euphytica, 2008)

Conservation of freshwater fish resources of India: new approaches, assessment and challenges - U. K. Sarkar; A. K. Pathak; W. S. Lakra (Biodiversity and Conservation, 2008)

Analysis of a village chicken production system and performance of improved dual purpose chickens under a subtropical hill agro-ecosystem in India - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Bijoy Chhetri; S. K. Ahmed; Santosh Haunshi (Tropical Animal Health and Production, 2008)

Endosulfan and Other Organochlorine Pesticide Residues in Maternal and Cord Blood in North Indian Population - Rahul Pathak; Sanvidhan G. Suke; Rafat S. Ahmed; A. K. Tripathi; Kiran Guleria; C. S. Sharma; S. D. Makhijani; Meenu Mishra; B. D. Banerjee (Bulletin of Environmental Contamination and Toxicology, 2008)

Stochastic Modeling of Progressive Failure in Heterogeneous Soil Slope - D. R. Pathak; H. N. Gharti; A. B. Singh; A. Hiratsuka (Geotechnical and Geological Engineering, 2008)

Modelling dust distributions in the atmospheric boundary layer on Mars - Peter A. Taylor; P-Y. Li; Diane V. Michelangeli; Jagruti Pathak; Wensong Weng (Boundary-Layer Meteorology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Dynamics of Organic Carbon and Microbial Biomass in Alluvial Soil With Tillage and Amendments in Rice-wheat Systems - B. Banerjee; P. K. Aggarwal; H. Pathak; A. K. Singh; A. Chaudhary (Environmental Monitoring and Assessment, 2006)

Treatment of chorea with levetiracetam - Theresa A. Zesiewicz; Amit Pathak; Kelly L. Sullivan; Mikhail Shamayev; Robert A. Hauser (European Journal of Clinical Pharmacology, 2006)

Impact of Post-Methanation Distillery Effluent Irrigation on Groundwater Quality - N. Jain; A. Bhatia; R. Kaushik; Sanjeev Kumar; H. C. Joshi; H. Pathak (Environmental Monitoring and Assessment, 2005)

“Medicamentation” of society, non-diseases and non-medications: a point of view from social pharmacology - T. B. Ngoundo Mbongue; A. Sommet; A. Pathak; J. L. Montastruc (European Journal of Clinical Pharmacology, 2005)

Soil Properties and Crop Productivity as Influenced by Flyash Incorporation in Soil - Naveen Kalra; M. C. Jain; H. C. Joshi; R. Chaudhary; Sushil Kumar; H. Pathak; S. K. Sharma; Vinod Kumar; Ravindra Kumar; R. C. Harit; S. A. Khan; M. Z. Hussain (Environmental Monitoring and Assessment, 2003)

Major Indian expeditions ofSaccharum complex - A. D. Pathak; H. M. Srivastava; N. Kulshreshtha (Sugar Tech, 2003)

The role of potassium in sustaining yields in a long-term rice-wheat experiment in the Indo-Gangetic Plains of Nepal - Regmi A.; Ladha J.; Pasuquin E.; Pathak H.; Hobbs P.; Shrestha L.; Gharti D.; Duveiller E. (Biology and Fertility of Soils, 2002)

Effect of Testosterone Suppression on the Pharmacokinetics of a Potent GnRH Receptor Antagonist - Eugenia A. Iatsimirskaia; Margaret L. Gregory; Kenna L. Anderes; Rosemary Castillo; K. Eric Milgram; David R. Luthin; Ved P. Pathak; Lance C. Christie; Haresh Vazir; Mark B. Anderson; John M. May (Pharmaceutical Research, 2002)

Mitigation of N 2 O emission from an alluvial soil by application of karanjin - Majumdar D.; Dutta A.; Kumar S.; Pathak H.; Jain M. (Biology and Fertility of Soils, 2001)

Enhanced Lipid Peroxide Levels in the Erythrocytes of Calves with Haemoglobinuria - A. Sahoo; R.C. Patra; N.N. Pathak; S.K. Dwivedi; P.K. Dash (Veterinary Research Communications, 2001)

Soil Amendment with Distillery Effluent for Wheat and Rice Cultivation - H. Pathak; H. C. Joshi; A. Chaudhary; R. Chaudhary; N. Kalra; M. K. Dwiwedi (Water, Air, & Soil Pollution, 1999)

Insect drift over the northern Arabian sea in early summer - S. C. Pathak; Vandana Kulshrestha; Arun Kumar Choubey; A. H. Parulekar (Journal of Biosciences, 1999)

Experimental biofilm and its application in malathion degradation - B. Kumari; A. Guha; M. G. Pathak; T. C. Bora; M. K. Roy (Folia Microbiologica, 1998)